Comparative pharmacokinetics between tenofovir disoproxil phosphate and tenofovir disoproxil fumarate in healthy subjects - Lee, Sangmi (Transl Clin Pharmacol, 2021)
Tenofovir is the representative treatment for human immunodeficiency virus and hepatitis B virus infection. This study was conducted to assess the pharmacokinetics (PKs) and safety characteristics after a single administration of tenofovir disoproxil phosphate compared to tenofovir disoproxil fumarate in healthy male subjects. An open-label, randomized, single administration, two-treatment, two-sequence crossover study was conducted in 37 healthy volunteers. Serial blood samples were collected up to 72 hours. Non-compartmental analysis was used to calculate the PK parameters. The 90% confidence intervals (90% CIs) of the geometric mean ratio (GMR) were calculated for comparing tenofovir disoproxil phosphate to tenofovir disoproxil fumarate. Safety assessments were performed including clinical laboratory tests, adverse events, etc. during the study. The GMR and 90% CIs were 1.0514 (0.9527–1.1603) for C(max) and 1.0375 (0.9516–1.1311) for AUC(last), respectively, and both fell within the conventional bioequivalence range of 0.8–1.25. Both tenofovir salt forms were tolerable. This study demonstrated that tenofovir disoproxil phosphate (292 mg) was bioequivalent to tenofovir disoproxil fumarate (300 mg).